The concept analysis of helplessness in nurses during the COVID‐19 pandemic: A hybrid model - Tooba Hoseini Azizi; Jamalodin Begjani; Alireza Arman; Akram Sadat Sadat Hoseini (Wiley, 2023)
Abstract Aim 'Helplessness' is one of the psychological concepts that exploring nurses' helplessness during the COVID‐19 pandemic can lead to timely intervention and empowerment of nurses. Design Concept development. Methods It was carried out using Schwartz‐Barcott and Kim's hybrid model. Results In the literature review, helplessness is characterized by anxiety symptoms (muscle tension, headache, anorexia and insomnia) and, to some extent, depression (loneliness, guilt, apathy and insensitivity). In the fieldwork, five categories were obtained, including antecedents of helplessness (the nature of the disease, professional responsibility, personal lifestyle disruption and social behaviours), attributes of helplessness (inability to do more for the patient, inability to control the situation, feeling of uselessness, frustration, giving up and uncertainty to continue), consequences of helplessness (increase clinical error, physical manifestations and psychological manifestations), strategies to reduce feelings of helplessness and the difference among helplessness, powerlessness and hopelessness. Conclusion Nurses' helplessness occurs when the nurse has no control over the situation and cannot change it.